Friday Morning Fever. Evidence from a Randomized Experiment on Sick Leave Monitoring in the Public Sector - Tito Boeri; Edoardo di Porto; Paolo Naticchioni; Vincenzo Scrutinio (Institute of Labor Economics (IZA), 2021)
This paper provides the first analysis of a population-wide controlled field experiment for home visits checking on sick leave in the public sector. The experiment was carried out in Italy, a country with large absenteeism in the public sector, and it concerned the universe of public employees. We exploit unique administrative data from the Italian social security administration (INPS) on sick leave and work histories. We find that receiving a home visit reduces the number of days on sick leave in the following 16 months by about 12% (5.5 days). The effect is stronger for workers who are found irregularly on sick leave (-10.2 days). We interpret our findings as a deterrence effect of home visits: workers being found irregularly on sick leave experience a decline of about 2% of their wage in the following 12 months. Uncertainty aversion (there is no automatism in these sanctions) can play a role in these results. Our estimates suggest that home visits are cost-effective: every Euro spent for the visits involves up to 10 Euros reductions in sick benefits outlays. We estimate the marginal value of public funds (MVPF) spent on home visits at about 1.13, which is significantly lower than estimates of MVPF of income taxes in the US.
Keywords: I12; J45; 330; sick leave; absenteeism; randomized trial